Factors influencing an eruption of teeth associated with a dentigerous cyst: a systematic review and meta-analysis - Marek Nahajowski; Sylwia Hnitecka; Joanna Antoszewska-Smith; Kornelia Rumin; Magdalena Dubowik; Michał Sarul (BMC, 2021)
Abstract Background A dentigerous cyst (DC) is a pathology embracing the crown of an unerupted tooth at risk of malignant transformation. The causal tooth is usually removed together with the cyst. However, if there are orthodontic contraindications for extraction, two questions arise. (1) Which factors favor spontaneous eruption? (2) Which factors imply the necessity of applying orthodontic traction? This systematic review aimed to identify factors conducive/inconducive to the spontaneous eruption of teeth after dentigerous cyst marsupialization. Methods In accordance with the PRISMA guidelines, the main research question was defined in the PICO format (P: patients with dentigerous cysts; I: spontaneous tooth eruption after surgical DC treatment; C: lack of a spontaneous tooth eruption after surgical DC treatment; O: determining factors potentially influencing spontaneous tooth eruption). The MEDLINE, EMBASE, and Cochrane Central Register of Controlled Trials databases were searched for keywords combining dentigerous/odontogenic/follicular cysts with teeth and/or orthodontics, as well as human teeth and eruption patterns/intervals/periods/durations. The following data were extracted from the qualified articles (4 out of 3005 found initially): the rate of tooth eruption after surgical treatment of the cyst, the age and sex of the patients, the perpendicular projection distance between the top of the tooth cusp and the edge of the alveolar process, tooth angulation, the root formation stage, the cyst area, and the eruption space. The articles were subjected to risk of bias and quality analyses with the ROBINS-I protocol and the modified Newcastle-Ottawa QAS, respectively. Meta-analyses were performed with both fixed and random effects models. The GRADE approach was used to evaluate the quality of the evidence. The systematic review was registered in PROSPERO under ID CRD42020189044. Results Nearly 62% of DC-associated premolars erupted spontaneously after cyst marsupialization/decompression. Young age (mean = 10 years) and root formation not exceeding 1/2 of its fully developed length were the factors likely to favor spontaneous eruption. Conclusion The small number of published studies, as well as their heterogeneity and the critical risk of bias, did not allow the creation of evidence-based protocols for managing teeth with DC after marsupialization. More high-quality research is needed to draw more reliable conclusions.